Linguistic witness identification techniques in the Alwaset dictionary Bab al-Ain as an applied model - سلمان, وداد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The view on the evidence has changed in the modern era, as it is no longer limited to eloquent speech used as evidence for the correctness of the language, but rather it has become an educational means that brings the reader closer to his surroundings and his language, and its primary function has become to clarify the meaning and express the new connotations and distinguish between them. Determine how the word is used in the current era. This study focuses on the interest in the issue of the evidence in the Alwaset dictionary, from a theoretical aspect that is known as the concept of the evidence and its functions in the dictionary, and examines the relationship of the evidence to the lexical meaning in ancient and modern times, and relies on an applied model, which is the chapter of Bab al– ain Ain to reach theoretical conclusions about the nature of the evidence and its importance. The extent of his ability to express the newly created connotations, distinguish between semantic relationships based on opposition, homogeneity, or commonality, and interpret cases of semantic, morphological, or grammatical change. It concludes with results and recommendations that may contribute to the development of this technique in the modern lexicon.